2007
DOI: 10.1055/s-2007-966349
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of patients with hereditary hemorrhagic telangiectasia with video capsule endoscopy: a single-center prospective study

Abstract: Small-bowel telangiectases were seen in the majority of patients with HHT and were evenly distributed throughout the small bowel. Telangiectases were observed in only a minority of patients who did not have HHT. Actively bleeding small-bowel telangiectases were located in the proximal and mid-small bowel in patients with HHT, all within reach of an enteroscope. We propose a cutoff point of at least five gastrointestinal telangiectases to support a diagnosis of HHT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 14 publications
0
19
0
5
Order By: Relevance
“…proctor et al, 27 using an enteroscope in 27 unselected HHT patients, found at least one telangiectasia in stomach/duodenum in all cases and also noted a strong correlation between the number of telangiectases in the stomach and duodenum as compared with the number in the jejunum. Chamberlain et al 20 compared a group of 38 consecutive HHT patients with a group of patients without HHT. VCE detected telangiectases evenly distributed throughout the small bowel in 81% of HHT patients versus 29% in non-HHT cases.…”
Section: Other Clinical Manifestationsmentioning
confidence: 99%
See 1 more Smart Citation
“…proctor et al, 27 using an enteroscope in 27 unselected HHT patients, found at least one telangiectasia in stomach/duodenum in all cases and also noted a strong correlation between the number of telangiectases in the stomach and duodenum as compared with the number in the jejunum. Chamberlain et al 20 compared a group of 38 consecutive HHT patients with a group of patients without HHT. VCE detected telangiectases evenly distributed throughout the small bowel in 81% of HHT patients versus 29% in non-HHT cases.…”
Section: Other Clinical Manifestationsmentioning
confidence: 99%
“…Before our study, few papers evaluated small-bowel telangiectases in HHT patients with video capsule endoscopy (VCE), detecting telangiectases evenly distributed throughout the small bowel in 56-86% of HHT patients. [19][20][21][22] The aim of this study was to use gastroduodenoscopy (EGd), capsule endoscopy, and colonoscopy (CS) to explore the entire GI tract of consecutive middle-aged or older HHT patients to assess the distribution, number, size, and type of telangiectases in relation to HHT genotype.…”
mentioning
confidence: 99%
“…12,13 Double-balloon enteroscopy appears more as a therapeutic and follow-up procedure after CE, according to an algorithm recently proposed by a panel of international experts. 14,15 Two studies 16,17 have described the prevalence, with CE, of small-bowel telangiectases in unselected patients with HHT but did not clarify the clinical consequences of these findings.…”
mentioning
confidence: 99%
“…À titre d'exemple, dans un travail comparatif portant sur 93 patients évalués par VCE pour une hémorragie digestive, où 38 patients étaient porteurs ou suspects d'une maladie de RO, comparés à 55 patients sans maladie de RO, la VCE détectait des angiodysplasies chez 80 % des patients porteurs de maladie de RO, alors qu'il en était mis en évidence chez 29 % des patients sans maladie de RO [10]. Dans ce travail, il était possible de définir un nombre minimum de cinq MAV détectées par la capsule, au niveau de l'intestin grêle pour suspecter ou évoquer le diagnostic de maladie de RO.…”
Section: Anomalies Mises En éVidence Par La Vidéocapsule Endoscopiqueunclassified